PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI PADA MATA PELAJARAN EKONOMI KELAS X IIS SMA LABORATORIUM UNIVERSITAS NEGERI MALANG - Nia Ayu Sriwahyuni; Mardono * (Universitas Negeri Malang, 2016)
This study aims to develop Economics instructional media in form of Economics Quiz educational game for the tenth grade students of Social Studies at SMA Laboratorium UM. The study also aimed to determine the feasibility and effectiveness of Economics Quiz educational game based on assessment of material experts, media experts and students. This study is a research & development (R & D) that are adapted and modified from the development model Borg and Gall). Based on data analysis that has been done, the percentage of the results of trials by media experts is 96%, material experts of 70.625%, small group of test results of 84.39% and the results of field trials of 86.62%. According to the guidelines for eligibility criteria for levels of media, then, this instructional media of educational game is already valid. Test media effectiveness reached 86.67% of students using instructional media reach a value above the standard passing grade (KKM). From these results, it can be concluded that the development of educational game based learning media is feasible and effective for use as a medium of learning. Keywords: Economics Instructional Media, Educational Game, Economics Quiz